Disruptive Innovation: An Intellectual History and Directions for Future Research - Christensen, Clayton M.; McDonald, Rory; Altman, Elizabeth J.; Palmer, Jonathan E. (Journal of Management Studies, 2018)
AbstractThe concept of disruptive innovation has gained considerable currency among practitioners despite widespread misunderstanding of its core principles. Similarly, foundational research on disruption has elicited frequent citation and vibrant debate in academic circles, but subsequent empirical research has rarely engaged with its key theoretical arguments. This inconsistent reception warrants a thoughtful evaluation of research on disruptive innovation within management and strategy. We trace the theory’s intellectual history, noting how its core principles have been clarified by anomaly‐seeking research. We also trace the theory’s evolution from a technology‐change framework—essentially descriptive and relatively limited in scope—to a more broadly explanatory causal theory of innovation and competitive response. This assessment reveals that our understanding of the phenomenon of disruption has changed as the theory has developed. To reinvigorate academic interest in disruptive innovation, we propose several underexplored topics—response strategies, performance trajectories, and innovation metrics—to guide future research.